Moral Education in the Formation of the Character of the Millennial Generation - Dadan Nurulhaq (UIN Sunan Gunung Djati Bandung, 2021)
The revolution in the field of information technology today has been able to change fundamentally the social order of society. The presence of information technology provides a lot of comfort for humans, but it also has a destructive side that threatens young generation. This paper through the study of literature aims to analyse the extent of the urgency and strategy of moral education for young generations of Muslims in the Disruption Era. The results of this study show the increasing importance of moral education for the younger generation, even becoming a primary need. This is due to a variety of morality problems that are increasingly widespread in this era with easy access to information technology. For that, the steps that need to be pursued to build individuals who have good morality, namely by: 1) providing a comprehensive understanding of the concept of morality; 2) giving and showing an example; 3) prevent learners to dissolve in pleasure and luxury; 4) strengthen the relationship between educators and students; 5) use a variety of methods in accordance with the conditions of students; and 6) building and controlling the environment of students (the surrounding environment and the influence of cyberspace).